2020
DOI: 10.34172/joddd.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics outcome of immediately restored single implants placed in extraction sockets in the anterior maxilla: A case series study

Abstract: Background . Immediate single implant placement and restoration (IIR) is recognized as a novel method and is the main request of many patients. This study was designed to evaluate the aesthetic outcomes of immediately restored single implants placed in extraction sockets in theanterior maxilla. Methods. In this case series study, 18 patients were selected from two private clinics after placing a single-tooth implant in the anterior maxilla. Immediate provisional crowns were delivered on the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…Gingival recession was reported as an exclusion criterion for Type 1A implant treatment protocol in 22 studies (Bittner et al, 2020; Block et al, 2009; Bruno et al, 2014; Cabello et al, 2013; Canullo et al, 2010; Cardaropoli et al, 2015, 2019; Cosyn et al, 2011, 2016; Cristalli et al, 2015; Di Alberti et al, 2012; Groisman et al, 2003; Kan et al, 2011; Khzam et al, 2014; Mangano et al, 2013; Migliorati et al, 2015; Raes, Eghbali, et al, 2018; Ross et al, 2014; Saedi Germi et al, 2020; Seyssens et al, 2020; Tarnow et al, 2014; Vidigal Jr. et al, 2017). Only two studies (Noelken, Moergel, Pausch, et al, 2018; Shanelec, 2005) reported that preoperative labial tissue deficiencies were present, and for which sub‐epithelial connective tissue grafting was performed in some of them.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gingival recession was reported as an exclusion criterion for Type 1A implant treatment protocol in 22 studies (Bittner et al, 2020; Block et al, 2009; Bruno et al, 2014; Cabello et al, 2013; Canullo et al, 2010; Cardaropoli et al, 2015, 2019; Cosyn et al, 2011, 2016; Cristalli et al, 2015; Di Alberti et al, 2012; Groisman et al, 2003; Kan et al, 2011; Khzam et al, 2014; Mangano et al, 2013; Migliorati et al, 2015; Raes, Eghbali, et al, 2018; Ross et al, 2014; Saedi Germi et al, 2020; Seyssens et al, 2020; Tarnow et al, 2014; Vidigal Jr. et al, 2017). Only two studies (Noelken, Moergel, Pausch, et al, 2018; Shanelec, 2005) reported that preoperative labial tissue deficiencies were present, and for which sub‐epithelial connective tissue grafting was performed in some of them.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the gaps varied between 1 and 4 mm, with most studies reporting placing biomaterial into the gap. Biomaterials utilized for socket grafting in conjunction with Type 1A protocols included deproteinized bovine bone mineral xenograft (22 studies—Arora & Ivanovski, 2018a; Arora & Ivanovski, 2018b; Bittner et al, 2020; Bonnet et al, 2018; Bruno et al, 2014; Canullo, Goglia, et al, 2009; Canullo & Rasperini, 2007; Cardaropoli et al, 2015; Cardaropoli et al, 2019; Cosyn et al, 2011; Cosyn et al, 2016; Cristalli et al, 2015; Degidi et al, 2013; Grandi et al, 2013; Grandi, Garuti, Samarani, et al, 2012; Groenendijk et al, 2017; Groenendijk et al, 2021; Khzam et al, 2014; Migliorati et al, 2015; Paul & Held, 2013; Seyssens et al, 2020; Valentini et al, 2010; Vidigal Jr. et al, 2017), autogenous bone (11 studies—Berberi, Noujeim, et al, 2014; Berberi, Sabbagh, et al, 2014; Ferrara et al, 2006; Ganeles et al, 2017; Groisman et al, 2003; Kan et al, 2011; Malchiodi et al, 2013; Mijiritsky et al, 2021; Noelken et al, 2011; Noelken, Moergel, Pausch, et al, 2018; Rosa et al, 2014), autogenous bone and xenograft mixture (six studies—Norton, 2011; Pieri et al, 2011; Shanelec, 2005; Slagter et al, 2021; Van Nimwegen et al, 2016; Zuiderveld et al, 2018), human allograft (six studies—Block et al, 2009; Bushahri et al, 2021; Kolerman, Nissan, Rahmanov, et al, 2016; Ross et al, 2014; Saedi Germi et al, 2020; Tarnow et al, 2014), alloplastic graft materials (three studies—Canullo et al, 2010; Lombardo et al, 2016; Mangano et al, 2012), and alloplastic/allograftor/...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations